Enzymatic synthesis of novel quercetin sialyllactoside derivatives. Issue 13 (3rd July 2019) - Darsandhari, Sumangala; Bae, Jae Yoon; Shrestha, Biplav; Yamaguchi, Tokutaro; Jung, Hye Jin; Han, Jang Mi; Rha, Chan-Su; Pandey, Ramesh Prasad; Sohng, Jae Kyung
Abstract: Quercetin and its derivatives are important flavonols that show diverse biological activity, such as antioxidant, anticarcinogenic, anti-inflammatory, and antiviral activities. Adding different substituents to quercetin may change the biochemical activity and bioavailability of molecules, when compared to the aglycone. Here, we have synthesised two novel derivatives of quercetin, quercetin-3- O - β -d -glucopyranosyl, 4′′- O -d -galactopyranosyl 3′′′- O - α - N -acetyl neuraminic acid i.e. 3′-sialyllactosyl quercetin (3′SL-Q) and quercetin-3- O - β -d -glucopyranosyl, 4′′- O - β -d -galactopyranosyl 6′′′- O - α - N -acetyl neuraminic acid i.e. 6′-sialyllactosyl quercetin (6′SL-Q) with the use of glycosyltransferases and sialyltransferases enzymes. These derivatives of quercetin were characterised by high-resolution quadrupole-time-of-flight electrospray ionisation mass spectrometry (HR-QTOF-ESI/MS) and 1 H and 13 C nuclear magnetic resonance (NMR) analyses. Abstract :